2004
DOI: 10.1016/j.ejvs.2004.06.009
|View full text |Cite
|
Sign up to set email alerts
|

The Management of Short Saphenous Varicose Veins: A Survey of the Members of the Vascular Surgical Society of Great Britain and Ireland

Abstract: The variation in management of short saphenous veins may be explained by the lack of definitive clinical trials in this area.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
56
0
2

Year Published

2007
2007
2017
2017

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(62 citation statements)
references
References 10 publications
4
56
0
2
Order By: Relevance
“…7,8 Preoperative duplex marking of the SPJ was done selectively, according to the result of the diagnostic scan by surgeons in the present study, as mirrored by national data. 9 As in other studies, preoperative duplex marking of the SPJ has not been shown to improve outcomes. 10,11 It has been suggested that SSV surgery is more hazardous than GSV surgery, and that recurrence is more common.…”
Section: Discussionmentioning
confidence: 96%
“…7,8 Preoperative duplex marking of the SPJ was done selectively, according to the result of the diagnostic scan by surgeons in the present study, as mirrored by national data. 9 As in other studies, preoperative duplex marking of the SPJ has not been shown to improve outcomes. 10,11 It has been suggested that SSV surgery is more hazardous than GSV surgery, and that recurrence is more common.…”
Section: Discussionmentioning
confidence: 96%
“…Open surgery may lead to iatrogenic damage to the common peroneal nerve and popliteal vein and artery, wound infection, and incomplete operations. 9 The latter may explain the high incidence of recurrence. It is noted that 9% of our procedures were required for persistent SPJ incompetence following inadequate conventional surgery.…”
Section: Discussionmentioning
confidence: 97%
“…4,13) The validity of the ligation level for SSV performed in the present study may be questionable as the thrombus as EHIT class 2 and 3 observed in the present study were both formed in the SSV stumps. As the lengths of the stumps in which the thrombus as EHIT class 2 and class 3 formed were 3.35 cm and 1.18 cm, respectively, the length of the stump in which the class 3 EHIT formed was relatively short.…”
Section: Thrombosis Of the Saphenous Vein Stumpmentioning
confidence: 41%